Freezing Strip Loin and Top Round Steaks Improves Warner-Bratzler Shear Force - R. McEwan; J. A. Unruh; T. A. Houser; T. G. O'Quinn; N. Bloedow; Christopher Vahl; S. Stroda (Kansas Agricultural Experiment Station Research Reports, 2016)
Postmortem aging of steaks is a common practice used to improve tenderness of beef steaks. The impact of proteolysis and improvement in tenderness due to aging varies among muscles. When designing research protocols, samples for Warner-Bratzler shear force (WBSF) are often frozen for later analysis because of convenience and time limitations. Freezing stops postmortem aging and allows for storage until meat can be cooked for WBSF and/or sensory analysis. However freezing meat may cause damage to cell membranes resulting in lower Warner-Bratzler shear force (improved mechanical tenderness), lower water holding capacity, and greater moisture loss during cooking. Several researchers have indicated that freezing strip loin (Longissimusmuscle) steaks may lower Warner-Bratzler shear force (improve tenderness) compared with those not previously frozen and sheared fresh. However, these results have been inconclusive for steaks from other muscles. Therefore, the objective of this study was to determine the effects of postmortem aging time and freezing on Warner-Bratzler shear force of six muscles from the beef hindquarter.
Keywords: tenderness; freezing; aging